A Comparison Of Hematocrit, MCV, MCH And MCHC Amount Between Rats On Vegan Dan Standard Diet After Routine Physical Exercise - Arwan Laeto; Rara Inggarsih; Septi Purnamasari; Masayu Farah Diba (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
ABSTRACT Background: The prevalence of non-communicable diseases in Indonesia, such as diabetes mellitus and obesity, continues to increase. The main factors are diet errors and mistakes in sport. Methods: This study used an in vivo experimental method with a pretest-posttest design with a non-equivalent group. The research sample consisted of 16 white rats, which were divided into two groups based on diet. The treatment given was in the form of dietary and routine physical exercise. Blood sampling was conducted to analyze hematocrit, MCH, MCV and MCHC levels. Results: The results showed that the change in body weight of the white rats on vegan diet was higher than the standard diet group. Routine physical exercise had significant effect on hematocrit levels in the standard white rats (p=0.034) compare to the vegan diet. In addition, routine physical exercise had a significant effect on MCV (p=0.026), MCH (p=0.027) and MCHC (p=0.026) levels in the vegan compared to the standard diet white rats. Conclusion: Changes in the number of hematocrits in the standard diet white rats is significant compared to the vegan diet group. Meanwhile, the levels of MCH, MCV and MCHC changed significantly in the white rats that were given a vegan diet compared to the white rats on a standard diet after routine physical exercise.